The Effect of Promotion Depth and Promotion Breadth on Distance Information Sharing with Moderation By Social Closeness (A Study of Rita Supermall's Instagram Account) - Simon Setiawan, Nolan Keane; Suliyanto , Suliyanto (CV. Publikasi Indonesia, 2025)
This study aims to analyze the effect of Promotion Depth and Promotion Breadth on Distant Sharing, moderated by Social Closeness, in the context of digital promotion on the Instagram account of Rita Supermall Purwokerto. This study adopts a quantitative approach with analytical methods and uses secondary data taken from 73 promotional posts taken by purposive sampling from the Instagram account during the period from January to March 2025. The Promotion Depth variable was measured based on the amount of discount offered in each post, while Promotion Breadth was measured based on the number of product categories promoted in each post. Distant Sharing was measured by examining the level of audience engagement in sharing promotional posts on their social networks. Meanwhile, Social Closeness was measured through social attributes in promotional content, such as cultural elements or personal closeness in the way promotions were delivered. The results show that Promotion Depth has a significant negative effect on Distant Sharing, meaning that the greater the discount offered, the less likely the audience is to share promotional content on their social networks. Conversely, Promotion Breadth does not have a significant effect on Distant Sharing, indicating that even though the promotion covers many product categories, this is not enough to encourage the audience to share information more widely. Furthermore, Social Closeness does not moderate the relationship between Promotion Depth and Distant Sharing, nor between Promotion Breadth and Distant Sharing, indicating that social factors are not strong enough to influence the audience's sharing behavior in the context of digital promotion. These findings provide insight for marketers on how the depth and breadth of promotion can influence information sharing behavior on social media and the importance of understanding the social factors that play a role in the process.